Hanceola yuanyangensis (Lamiaceae, Nepetoideae), a new species from Yunnan, China - Chen, You-Sheng; Xiang, Chun-Lei; Wu, Jian-Yong; Liao, Jun-Jie; Zheng, Hai-Lei (Phytotaxa, 2021)
Hanceola is a genus of nine herbaceous or subshrubby species ranging from southern China to Northern Vietnam. Hanceola yuanyangensis, a new species from Yuanyang County, Yunnan, southwest China, is here described and illustrated. It is morphologically most similar to H. tuberifera, but differs in characters of tuber, corolla, style and phenology.